Encouraging Dialogue on Academic Integrity: A Scenario-Based Approach - Tooher, Michelle; Greene, Mairead (Journal of Academic Writing, 2025)
This paper recommends that explicit value be placed on promoting dialogue among staff and students with respect to academic integrity in higher education. A detailed literature review revealed a notable lack of literature on resources and practices for professional development of staff on academic integrity or the importance of engaging academic staff in such training. Through the authors’ experience in developing and facilitating workshops, they have designed a flexible approach to academic integrity professional development for academic staff that highlights the importance of discussion and communication. Throughout this workshop development, scenarios were created to prompt discussion on a wide range of academic integrity issues (including Generative Artificial Intelligence (GenAI)). In total, 18 workshops addressing academic integrity have been run by the authors and attended by 180 staff and 85 students at local, national, and international levels. This experience-based paper situates the need for professional development on academic integrity within the current literature and shares the evolution of the authors’ training workshops and resource development. Readers are encouraged to use the resources in their own contexts to prompt dialogue within their institutions on academic integrity.